COVID-19: A new chapter in the loneliness epidemic - ZHU, Nancy (Institutional Knowledge at Singapore Management University, 2020)
We live in an era of increasing innovation and connectivity. It's said that we have the world is at our fingertips, with social media granting us the ability to link up quickly and easily with anyone across the globe. Yet the irony is that loneliness is a trusty companion in a modern and interconnected world.